Historiar el mal en Venezuela El mal como instrumento político en Venezuela (1999-2022) - Jo-ann Peña-Angulo (Caravelle)
This paper aims to study the historical experience of evil in Venezuela. From the history of the present time and the regimes of historicity, we inquire about the pernicious nature of the political and ideological mechanisms that, instituted by Chavismo, seek the subordination of the other, especially of those who oppose and resist it. Memory, testimonies and documentation thus allow us to show the institutionalization of violence and the use of evil as a political instrument.